Director with foreign experience, CSR, profitability, leverage on tax avoindance: Firm size as moderate - Pratiwi, Winna; Rachmat, Radhi Abdul Halim (WIM Solusi Prima, 2025)
This study investigates the influence of several key variables namely director with foreign experience, Corporate Social Responsibility (CSR), profitability, and leverage on tax avoidance, firm size positioned as a moderating factor. The research is centered on manufacturing firms within the basic and chemical industry sectors, specifically those engaged in the pulp and paper segment, and listed on the Indonesia Stock Exchange (IDX) between 2014 until 2023. Profitability is gauged by ROE, leverage is quantified using DER, and the degree of tax avoidance is measured through the ETR. This study applies a verificative research approach, focusing on a target population of nine manufacturing companies. Through the implementation of an unbalanced panel sampling technique, 80 firm-year observations were ultimately selected as the research sample. Secondary data were sourced from the IDX platform and official company websites, encompassing published financial statements and annual reports over the defined research period. Data analysis was carried out using panel data regression techniques with the assistance of E-Views version 13 software. The empirical outcomes highlight that directors with overseas exposure, active CSR engagement, and higher profitability are associated with lower levels of tax avoidance behavior. Conversely, companies with greater leverage tend to exhibit more aggressive tax minimization strategies. Firm size significantly moderates these relationships: it amplifies the negative impact of foreign directorships, CSR initiatives, and profitability on tax avoidance, while reinforcing the positive influence of leverage on such behavior. These findings indicate that internal factors drive firms' tax strategies, with firm size either amplifying or reducing their impact.